Security Enforced Mediation Systems for Data Integration - Yang, Li; K. Ege, Raimund (INFOCOMP Journal of Computer Science, 2006)
Mediation techniques support integrated query processing among heterogeneous databases. While such techniques help data sharing among different distributed sources, they increase the risk for data security, such as violating access control rule. Successful protection of information by an effective access control mechanism is a basic requirement for data integration among heterogeneous sources. How to protect the object with fine-granularity, how to support the access control specification at different points, and how to support the semantic heterogeneity in the access control become the major challenges in the data protection of the mediation system. Currently few existing approaches address all three security challenges inmediation system. With the purpose of solving the aforementioned challenges faced by the access control in mediation system, we present an architectural and practical solution to assure the data security in the process of data integration from different sources.